Incidence of the public policy of the integral management of solid waste, regarding cigarette butts and filters, in the city of Bogotá (2023)
The purpose of this essay is to expose the environmental problems derived from the inadequate disposal of solid waste, specifically those that are not biodegradable such as cigarette butts and cigarette filters; it refers to figures, positions of international organizations that recognize the environmental situation, and quotes academic documents from Colombian universities that have tried to describe this public problem in the city of Bogotá D.C. and generate debates around it. In accordance with this, reference is made to: i) the instruments used by national and district authorities, to address this problem, which range from the enactment of a national policy for integral solid waste management (CONPES 3874 of 2016) to an Agreement of the Council of Bogota (Agreement No. 704 of 2018), to then make considerations on the suitability, relevance and congruence of such instruments and strategies to prevent and/or solve the environmental pollution problem caused by throwing cigarette butts and filters on the streets and sidewalks of the city of Bogotá; and ii) the actors, who have responsibility and competence in creating, designing and implementing public policy aimed at thoroughly addressing the situation under discussion. Finally, a series of local and international initiatives are presented, which are success stories and show that this environmental problem can be prevented through public policies that promote environmental education and culture, as well as by designing a solid waste management model that allows its final use.